LEMBAGA PENYIARAN PUBLIK INDONESIA DALAM PERSIMPANGAN IDEALISME VS EKONOMI POLITIK MEDIA - Nurul Adji Dwi Wulandari (Interaksi: Jurnal Ilmu Komunikasi, 2016)
AbstractTVRI status changing into public service broadcasting, both for its central broadcast station and its local broadcast station in 2003 brought many significant changes in these oldest television broadcast station in Indonesia. One of the most significant changes that can be traced is on its funding system. As a public service broadcasting,  TVRI was guaranted to obtain  the operational fund through the state or regional budget funding mechanisme. The government also promised that TVRI will be given oppportunity to operate like private broadcast station in order to gain maximal profit which has stated through government regulations and broadcasting acts. Inevitably consequent of this funding practice system, has put TVRI to  always depend on goverment in order to operate daily. In the other hand, this funding system also will make TVRI gain a lot of profit and income commercially. These mixed funding systems indicate that there are political economy interest behind the new status that has been granted for TVRI. The problem is located on the practice of this kind model of funding on a public service broadcasting that will make the neutrality and independency of this public service broadcasting to be questioned. The remaining quetions, Will TVRI come to its own realazation to visualize its idealism to be the true public service broadcasting that serves public needs or will TVRI be crushed by the economy politic media policy and serve those who has a power that control the media Keywords:  media, public service broadcasting, economy politic media, broadcast  act